FEATURES OF MENTAL AND BEHAVIOR DISORDERS AMONG MILITARY PERSONNEL IN PEACE TIME AND SPECIAL PERIOD AND ITS MEDICAL AND SOCIAL IMPORTANCE - Sereda, I.K.; Lopin, E.B.; Shvets, A.V. (World of Medicine and Biology, 2022)
A retrospective analysis of statistical data on the level, structure, dynamics of the general, hospitalized morbidity rate of mental disorders among military personnel of Ukrainian Armed Forces and health status dismissal based on long-term observation data (2008–2017) as well as comparison of indicators of the period 2008–2013 and 2014–2017 on the basis of official statistical reporting has been performed. It was discovered that in the structure of the total incidence of military personnel of Ukrainian Armed Forces on the class V for the period 2014–2017 there was a redistribution of all categories of military personnel in comparison with 2008–2013 (in the case of officers as well as contract servicemen, the overall morbidity decreased reliably). It has been established that, starting from 2014, the rates of health-related layoffs for class V diseases increased among officers with the highest rates by 2015 (in comparison with 2013 at 7 times) and the contract servicemen by 2016 (as compared to 2013, 5.3 times) with subsequent decrease. The revealed features of mental health disorders in military personnel and their consequences on the basis of long-term observation are priority for development and the introduction of an effective psycho-medical intervention system in defense forces based on NATO standards.